Effect of Erythropoietin on the Expression of Murine Transferrin Receptor 2 - Berezovsky, Betty; Báječný, Martin; Frýdlová, Jana; Gurieva, Iuliia; Rogalsky, Daniel Wayne; Přikryl, Petr; Pospíšil, Vít; Nečas, Emanuel; Vokurka, Martin; Krijt, Jan (International journal of molecular sciences, 2021)
Erythropoietin (EPO) downregulates hepcidin expression to increase the availability of iron; the downregulation of hepcidin is mediated by erythroferrone (ERFE) secreted by erythroblasts. Erythroblasts also express transferrin receptor 2 (TFR2); however, the possible role of TFR2 in hepcidin downregulation is unclear. The purpose of the study was to correlate liver expression of hepcidin with the expression of ERFE and TFR2 in murine bone marrow and spleen at 4, 16, 24, 48, 72 and 96 h following administration of a single dose of EPO. Splenic Fam132b expression increased 4 h after EPO injection; liver hepcidin mRNA was decreased at 16 h. In the spleen, expression of TFR2 and transferrin receptor (TFR1) proteins increased by an order of magnitude at 48 and 72 h after EPO treatment. The EPO-induced increase in splenic TFR2 and TFR1 was associated with an increase in the number of Tfr2- and Tfr1-expressing erythroblasts. Plasma exosomes prepared from EPO-treated mice displayed increased amount of TFR1 protein; however, no exosomal TFR2 was detected. Overall, the results confirm the importance of ERFE in stress erythropoiesis, support the role of TFR2 in erythroid cell development, and highlight possible differences in the removal of TFR2 and TFR1 from erythroid cell membranes.
Keywords: Liver; kultivované buňky; játra; exozómy; Receptors, Transferrin; Male; erythroferrone; Hepcidins; cytokiny; svalové proteiny; Erythroblasts; exosomes; myši inbrední C57BL; mužské pohlaví; Mice; Cytokines; hepcidin; slezina; Erythropoietin; Cells, Cultured; transferrin receptor; erythropoetin; zvířata; receptory transferinu; Exosomes; Muscle Proteins; myši; erytroblasty; Spleen; Mice, Inbred C57BL; hepcidiny; Animals